Quality of Life After Myocardial Infarction as a Function of Temperamental Traits, Stress Coping Styles, and Posttraumatic Stress Disorder Symptoms - Burnos, Agnieszka; Wrzosek, Maria (Frontiers in Psychiatry, 2022)
The presented study aims to explore the relationship between quality of life after myocardial infarction and factors such as temperamental traits, stress coping, and posttraumatic stress disorder (PTSD) symptoms. Ninety-six participants, including 51 females and 45 males aged 24–85 years, who have survived ST-elevation myocardial infarction were asked to complete the Formal Characteristics of Behavior—Temperament Inventory, Coping Inventory for Stressful Situations, PTSD Inventory, and Quality of Life SF-36 questionnaire. According to the obtained results, a lower level of briskness and sensory sensitivity, as well as a higher level of perseverance and endurance, correlates with a higher level of emotion-oriented coping, whereas a higher level of perseverance, endurance, and activity correlates with a higher level of avoidant-distracted coping. Moreover, a higher level of briskness and activity is correlated with a higher level of avoidant-social coping. A higher level of emotion-oriented and avoidant-distracted coping is, in turn, associated with a higher intensity of PTSD symptoms, whereas a higher level of avoidant-social coping correlates with lower intensity of PTSD symptoms. Furthermore, a higher level of avoidant-distracted coping is correlated to a better physical quality of life, whereas higher levels of endurance and activity are associated with a better emotional quality of life. Also, the more severe the PTSD symptoms, the lower quality of life in general. Contrastingly, higher sensory sensitivity and briskness correlate with better quality of life. The meaning of other temperamental traits, however, is more ambiguous. Nevertheless, the findings support the model of psychological processes in which the subsequent stages are temperament, coping, PTSD, and quality of life.